Tributaries and peripheries of the Ottoman Empire (Leiden)
xi, 336 sayfa
Keywords: “Tributaries and Peripheries of the Ottoman Empire offers thirteen studies on the relationship between Ottoman tributaries with each other in the imperial framework, as well as with neighboring border provinces of the empire’s core territories from the fifteenth to the eighteenth centuries. A variety of surveys related to the Cossack Ukraine, the Crimean Khanate, Dagestan, Moldavia, Ragusa, Transylvania, Upper Hungary and Wallachia allow the reader to see hitherto less known subtleties of the Ottoman administration’s hierarchic structures and the liberties and restrictions of the office-holders’ power. They also shed light upon the strategies of coalition-building among the elites of the tributaries as well as the core provinces of the border zones, which determined their cooperation, but also the competition between them” --